The Silver Lining of Higher Education Exit Exams—Global Perspectives: A Systematic Review - Teshome, Samson Worku (International Journal of Pedagogy, 2025)
Exit exams in higher education serve as a critical tool to assess students' proficiency and ensure they meet academic and professional standards before graduation. These exams evaluate critical thinking, subject mastery, and alignment with program learning outcomes, while also providing insights into curriculum strengths and weaknesses. This systematic literature review synthesizes the advantages and disadvantages of exit exams by analyzing 24 peer-reviewed studies sourced from databases such as ERIC, Google Scholar, and Wiley. The review follows PRISMA guidelines and employs PICO to structure research questions, ensuring methodological rigor. The significance of this study lies in its comprehensive analysis of exit exams' dual impact, offering valuable insights for policymakers, educators, and institutions. Findings reveal that exit exams enhance quality assurance, standardize assessments, and improve student performance, but they also pose challenges such as increased stress, equity concerns, and potential curriculum narrowing. By highlighting best practices and pitfalls, the review aids in designing balanced assessment strategies that maximize benefits—such as accountability and employability—while mitigating drawbacks like student anxiety and inequity. This contributes to ongoing debates about educational quality and reform, providing evidence-based recommendations for optimizing exit exam implementation in higher education.